Analysis of Service Broker Policies in Cloud Analyst Framework - Sankla, Ashish (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The aim of the paper is to analyze different service broker policies that can be used with cloud and are been used in cloud analyst. With the advancement in the cloud computing technologies cloud is becoming more popular these days. With the increase in the number of clients and servers there is also arising needs of service broker. Broker is been used to assign a server to the client on clients request. Here I will first discuss about cloud computing, and then cloud analyst and the different broker policies embedded in it under round robin load balancing policy. Then with the help of simulation results will propose the best broker policy on the basis of performance.